Climate Finance for Agriculture and Livelihoods - Foster K; Neufeldt, Henry; Franks P; Diro, R.; Munden, L; Anand M; Wollenberg, Eva Karoline (World Agroforestry Centre, 2013)
This brief addresses the major challenges and opportunities to financing climate change mitigation and adaptation pathways for smallholder farmers in developing nations. It underlines the need for an innovative and integrated approach to climate finance that can connect rural farmers to public and private finance at the global level. Lastly, it provides recommendations for future actions that can meet adaptation, development and mitigation aims.